Microstructure through an ice sheet - Binder, Tobias; Weikusat, Ilka; Freitag, Johannes; Garbe, Christoph S.; Wagenbach, Dietmar; Kipfstuhl, Sepp (Materials science forum)
Ice cores through an ice sheet can be regarded as a sample of a unique natural deformation experiment lasting up to a million years. Compared to other geological materials forming the earth‘s crust, the microstructure is directly accessible over the full depth. Controlled sublimation etching of polished ice sections reveals pores, air bubbles, grain boundaries and subgrain boundaries at the surface. The microstructural features emanating at the surface are scanned. A dedicated method of digital image processing has been developed to extract and characterize the grain boundary networks. First preliminary results obtained from an ice core drilled through the Greenland ice sheet are presented. We discuss the role of small grains in grain size analysis and derive from the shape of grain boundaries the acting driving forces for grain boundary migration.